The utility of immunofluorescence in diagnosing dermatological lesions and its correlation with clinical and histopathological diagnosis in a tertiary health care setup - Rajeswari Thivya Dhanabalan (Indian Journal of Dermatopathology and Diagnostic Dermatology, 2016)
Context: Immunofluorescence (IF) is an immunological technique which is used for identifying antibodies against antigens that are bound to tissues or those circulating in body fluids. This study is an attempt to evaluate the dermatological lesions such as noninfectious vesiculobullous lesions, connective tissue disorders, vasculitis, and lichen planus using histopathology techniques and direct IF (DIF) studies. Furthermore, an attempt was made to evaluate the diagnostic utility of the IF technique in our hospital. Aims: (1) To determine the utility of IF in the diagnosis of skin lesions. (2) To correlate IF with histopathological findings. Settings and Design: A cross-sectional, observational study. Subjects and Methods: The present study was conducted in the Pathology Department, Coimbatore Medical College, Coimbatore, from August 2012 to August 2013. Fifty cases received during the period were included in our study. Two skin biopsies for each case - one in formalin for routine histopathological examination and other in phosphate buffer solution for IF studies - were received. Statistical Analysis Used: Fisher's exact value, mean, and coefficient of mean were calculated. Results: The lesions were diagnosed by both light microscopy and IF study. Out of fifty cases, 42 cases were positive with the IF technique and the overall sensitivity of IF was 84% in our study. When histopathological and IF findings were correlated, statistically significant two-tailed P = 0.0130 was obtained. Both light microscopic findings and IF findings complemented each other in our study. IF proved to be a necessary supplementary technique to both clinical and histopathological examinations, especially in cases of diagnostic dilemmas. Conclusions: IF is a rapid diagnostic procedure. IF was useful in early diagnosis, treatment, and monitoring of various disorders in our study. Positive and negative DIF had prognostic significance in certain cases. Clinicopathological correlation along with DIF studies proved to be a powerful tool in definite diagnosis of the skin lesions.